Hepatic microcirculation in the perfused cirrhotic rat liver. - Varin, F (1985)
Liver microcirculation in the perfused rat liver was assessed by the multiple indicator dilution technique. Comparative studies were carried out in noncirrhotic rats and in rats with cirrhosis secondary to chronic exposure to phenobarbital and carbon tetrachloride. The alterations of the sinusoidal bed were characterized by changes in the displacement of hepatic venous outflow curves of various diffusible substances (labeled albumin, sucrose, and water) relative to that of labeled erythrocytes (vascular reference). Outflow recoveries of lidocaine (a substance that penetrates the liver cell membrane freely and completely) and of labeled microspheres (15 microns diam) were also appraised. In all cirrhotic rats, unimodal erythrocytes and albumin curves were obtained. The sinusoidal space was significantly decreased when compared with normal rats (P less than 0.001) and the total space accessible to albumin became progressively restricted. In seven cirrhotic rats, the profiles of labeled sucrose and water curves were compatible with a flow-limited diffusion and the total distribution volumes were not significantly different from values found in noncirrhotic rats (P = NS), which indicates that sucrose and water were still able to diffuse into an extravascular space not accessible to albumin. In the other cirrhotic rats, labeled sucrose and water curves showed progressive bimodal changes not compatible with a flow-limited diffusion. Such alterations were not due to large intrahepatic shunts, since only 0.25% of the 15-microns microspheres were recovered in the outflow of cirrhotic rats. However, an early lidocaine outflow peak related in time to the peak erythrocyte curve was observed in cirrhotic, but not in noncirrhotic, rats. Lidocaine recovery varied greatly in cirrhotic rats and appeared to increase as the liver disease progressed. These data can be explained by capillarization of sinusoids and/or by the development of channels with poor permeability. Electron microscopic observations of these rat livers favored the latter. Thus, in cirrhotic rat liver, two kinds of alteration are likely: (a) the vascular space is decreased with collagenization of the extravascular space, limiting the diffusion of large molecules such as albumin; and (b) small channels with poorly permeable walls develop, limiting the diffusion of small molecules such as lidocaine, sucrose, and water. Large intrahepatic shunts are not a common feature.